The Mediating Role of Fear of Missing Out (FOMO) and Loneliness in the Relationship Between Internet Addiction and Rumination in Adolescents - Kalantari, Elham; Bakhtiari Saeed , Farima; Samadi, Parisa (Mental Health and Lifestyle Journal, 2024)
This study aimed to investigate the mediating roles of fear of missing out (FOMO) and loneliness in the relationship between internet addiction and rumination among adolescents. A descriptive correlational design was employed with a sample of 388 adolescents from Tehran, selected based on Morgan and Krejcie’s sampling table. Participants completed standard self-report instruments measuring internet addiction, FOMO, loneliness, and rumination. Descriptive statistics and Pearson correlation coefficients were analyzed using SPSS-27, while structural equation modeling (SEM) was conducted using AMOS-21 to test the mediating roles of FOMO and loneliness in the proposed model. The model fit was assessed using indices including Chi-square, RMSEA, CFI, TLI, GFI, and AGFI. Internet addiction was positively and significantly correlated with FOMO (r = .59, p < .001), loneliness (r = .41, p < .001), and rumination (r = .52, p < .001). SEM results confirmed the direct effect of internet addiction on rumination (β = 0.23, p < .001) as well as significant indirect effects through FOMO (β = 0.28, p < .001) and loneliness (β = 0.20, p < .001). The total effect of internet addiction on rumination was substantial (β = 0.71, p < .001). The structural model demonstrated good fit indices (χ²/df = 2.06, CFI = 0.96, RMSEA = 0.053, GFI = 0.94, TLI = 0.95). The findings suggest that both FOMO and loneliness serve as significant mediators in the relationship between internet addiction and rumination in adolescents. These results highlight the need for targeted interventions addressing emotional vulnerabilities and digital behaviors to mitigate cognitive risks associated with excessive internet use.